2021
DOI: 10.3389/fphys.2021.697121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Skeletal Muscle DNA Methylation and Transcriptome of the Chicken Embryo at Different Developmental Stages

Abstract: DNA methylation is a key epigenetic mechanism involved in embryonic muscle development and plays an important role in early muscle development. In this study, we sought to investigate the effects of genome-wide DNA methylation by combining the expression profiles of the chicken embryonic muscle. Genome-wide DNA methylation maps and transcriptomes of muscle tissues collected from different embryonic development points (E7, E11, E17, and D1) were used for whole-genome bisulfite sequencing (WGBS) and RNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the early development of muscles, DNA methylation is a significant factor that cannot be ignored [ 22 , 48 , 49 ]. Different studies had found that DMGs were significantly related to actin filament depolymerization, skeletal muscle satellite cell proliferation and muscle organ development while CFL2 negatively regulated the proliferation of chicken skeletal muscle satellite cells and induced cell apoptosis [ 50 ] (Fig. 3 b).…”
Section: The Mechanism Of Dna Methylation During Muscle Development I...mentioning
confidence: 99%
“…In the early development of muscles, DNA methylation is a significant factor that cannot be ignored [ 22 , 48 , 49 ]. Different studies had found that DMGs were significantly related to actin filament depolymerization, skeletal muscle satellite cell proliferation and muscle organ development while CFL2 negatively regulated the proliferation of chicken skeletal muscle satellite cells and induced cell apoptosis [ 50 ] (Fig. 3 b).…”
Section: The Mechanism Of Dna Methylation During Muscle Development I...mentioning
confidence: 99%
“…Myogenic cells are the precursors of myoblasts, and their proliferation and differentiation determine the growth and development of skeletal muscle [9,10]. This stage of muscle development determines the number and structure of muscle fibers in domestic animals [11]. In phase II, postnatal muscle growth and development is closely related to the proliferation and differentiation of stem and progenitor cells (satellite cells) [12][13][14].…”
Section: Overview Of Skeletal Muscle Growth and Development In Animalsmentioning
confidence: 99%
“…The proliferation and apoptosis of satellite cells during the development of skeletal muscles in chicken embryos were regulated by the DNA methylation of Cfl2 according to whole genome bisulfite sequencing (WGBS) analysis [1]. In addition, the DNA methylation/Sp1/Igf2bp3 axis was involved in porcine skeletal myogenesis [15].…”
Section: Of 15mentioning
confidence: 99%
“…Ensuring the supply of high-quality animal protein requires the highly efficient development of husbandry in the poultry industry, which includes chickens, ducks, and geese [1,2]. The production and quality of muscle during growth periods are influenced by the embryonic stages [3].…”
Section: Introductionmentioning
confidence: 99%